2015
DOI: 10.1016/j.neo.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Insulin-Like Growth Factor Binding Proteins Correlates With Tumor-Promoting Effects of Matrix Metalloproteinase 9 in Breast Cancer

Abstract: The stroma of breast cancer can promote the disease’s progression, but whether its composition and functions are shared among different subtypes is poorly explored. We compared stromal components of a luminal [mouse mammary tumor virus (MMTV)–Neu] and a triple-negative/basal-like [C3(1)–Simian virus 40 large T antigen (Tag)] genetically engineered breast cancer mouse model. The types of cytokines and their expression levels were very different in the two models, as was the extent of innate immune cell infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…While our results implicated a positive feedback regulatory loop of AMPKα signaling, the possible involvement of other kinase signaling pathways, and up- or downstream mediators underlying this regulation, such as phosphorylation and regulation of IGF-1 receptor [47, 48], regulation of IGFs [49], forkhead box class O (FOXO) [50], and hypoxia-inducible factor (HIF) [51], among others, required to be elucidated in the future studies. In addition to inhibiting IGF effects [52], IGFBP1 also showed to suppress cancer cell proliferation, invasiveness and motility via stimulating or inhibiting several critical downstream genes and/or proteins [51, 53], which highlighted a tumor suppressor role of IGFBP1. Consistent with these, our results implied that the induction of IGFBP1 expression was required in stimulating the emodin-inhibited NSCLC growth.…”
Section: Discussionmentioning
confidence: 99%
“…While our results implicated a positive feedback regulatory loop of AMPKα signaling, the possible involvement of other kinase signaling pathways, and up- or downstream mediators underlying this regulation, such as phosphorylation and regulation of IGF-1 receptor [47, 48], regulation of IGFs [49], forkhead box class O (FOXO) [50], and hypoxia-inducible factor (HIF) [51], among others, required to be elucidated in the future studies. In addition to inhibiting IGF effects [52], IGFBP1 also showed to suppress cancer cell proliferation, invasiveness and motility via stimulating or inhibiting several critical downstream genes and/or proteins [51, 53], which highlighted a tumor suppressor role of IGFBP1. Consistent with these, our results implied that the induction of IGFBP1 expression was required in stimulating the emodin-inhibited NSCLC growth.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors in this model have high numbers of infiltrating neutrophils and high expression of CXCL1 (22). Like 4T1 cells, C3(1)-Tag primary cancer cells induced NETs when co-cultured with mouse neutrophils (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, because we identified G-CSF as a critical factor in the induction of NETs by cancer cells, it is possible that cancer cell expression of G-CSF could identify patients at risk of developing NET-promoted metastasis. Both 4T1 cells and C3(1)-Tag tumors express high levels of G-CSF (22, 35), and they are both models of triple-negative breast cancer. Higher amounts of G-CSF are found in human patient samples of triple-negative breast cancers than of other subtypes (34).…”
Section: Discussionmentioning
confidence: 99%
“…Report showed that excess of IGFBP1 inhibited growth of breast cancer cells via inhibition of IGF receptor 1 binding to IGFs [29]. High expression of IGFBP mRNA was strongly correlated with better survival in breast cancer mouse model [30]. We previously observed that ursolic acid, a natural pentacyclic triterpenoid, and emodin, one anthraquinones constituents derivative isolated from the roots of rheum palmatuma, inhibited growth of hepatocellular carcinoma and lung cancer cells through induction of IGFBP1 gene expression, suggesting tumor suppressing role of this molecule [31, 32].…”
Section: Introductionmentioning
confidence: 99%